el-Miʿyârü’l-muʿrib ve’l-câmiʿu’l-muğrib ʿan fetâvâ ʿulemâʾi İfrîkıyye ve’l-Endelüs ve’l-Mağrib - 880-01 Venşerîsî, 1430?-1508. ([Fas] [Fas])
<7> cilt (5. c. 355 sayfa, [16] sayfa fihrist ; 6. c. 443 sayfa, [14] sayfa fihrist ; 7. c. 8, 3 sayfa fihrist, 344 sayfa ; 8. c. 8, 8, 8 sayfa fihrist, 308 sayfa ; 9. c. 8, 8, 8, 8 sayfa fihrist, 479 sayfa ; 11. c. [5], 295 sayfa ; 12. c. 8, 262, [2] sayfa)